PENGARUH UMUR TERHADAP PENJANTANAN LARVA IKAN LELE DUMBO (Clarias gariepinus) YANG DIRENDAM MENGGUNAKAN HORMON METIL TESTOTERON ALAMI (The Influence of Age on Masculinization of Clarias gariepinus Larvae Immersed by Methyl Testosterone Natural Hormone) - Hattanul Mulia; Rosmaidar Rosmaidar; Dasrul Dasrul; Dwinna Aliza; Dian Masyitha; Sugito Sugito (Universitas Syiah Kuala, 2016)
This research aims to examines the influence of age on masculinization of Clarias gariepinus larvae immersed by methyl testosterone (MT) natural hormone. This research used 270 catfish larvae divided into 3 groups of age those are 5, 10, and 20 days. The research implemented complete random design (CRD). Immersion was performed using methyl testosterone hormone at the dose of 0.25 g/L for 20 hours. Observation of fish was done after 60 day-old fish. Data obtained was analyzed using one-way analysis of variance The average percentages of male-sex catfish after immersing in natural MT on group I, II, and III were 97.67, 91.07, and 86.67%, respectively. The results showed that the age of the larvae did not affect significantly (P0.05) on the percentage of male sex of Clarias gariepinus. The average percentage of male sex in 5 days age group was higher than 10 and 20 days age group. In conclusion, the masculinization of Clarias gariepinus larva immersed by MT natural hormone is not influenced by age of fish before dipping.